2023
DOI: 10.2217/fca-2023-0014
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Dapagliflozin in the Whole Spectrum of Heart Failure in Clinical Practice: The RICA Registry

Abstract: Aims: To determine the projected benefits of dapagliflozin after an acute heart failure (HF) event in Spain. Methods: A multicenter and prospective study that included subjects aged 50 years or older consecutively admitted with HF to internal medicine departments in Spain. The projected clinical benefits of dapagliflozin were calculated via pooled analysis of the DAPA-HF and DELIVER trials. Results: A total of 5644 subjects were analyzed, of whom 79.2% were eligible for dapagliflozin, according to criteria of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, patients had numerous comorbid conditions. In the RICA registry, which included patients aged ≥50 years admitted with HF to internal medicine departments in Spain between 2008 and 2019, the mean age was 80 years, up to a third of patients were in functional class III, more than 60% had HFpEF, and comorbidity was very common [ 17 ]. Various studies have indicated that in clinical practice, a high number of patients with HF would be eligible for treatment with SGLT2i [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients had numerous comorbid conditions. In the RICA registry, which included patients aged ≥50 years admitted with HF to internal medicine departments in Spain between 2008 and 2019, the mean age was 80 years, up to a third of patients were in functional class III, more than 60% had HFpEF, and comorbidity was very common [ 17 ]. Various studies have indicated that in clinical practice, a high number of patients with HF would be eligible for treatment with SGLT2i [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robust evidence from clinical trials and sub-studies has demonstrated that dapagliflozin reduces not only HF (re-)hospitalizations, but also cardiovascular mortality (NNT = 68) and all-cause death (NNT = 67) in the whole spectrum of HF, without a loss of efficacy according to ejection fraction [92]. On the other hand, different studies have shown that a great proportion of patients with HF in clinical practice are eligible for dapagliflozin according to the DAPA-HF and DELIVER criteria [102][103][104][105][106][107][108]. In addition, the full implementation of dapagliflozin in real-life populations would prevent/postpone new worsening HF events or even death [102,[106][107][108].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different studies have shown that a great proportion of patients with HF in clinical practice are eligible for dapagliflozin according to the DAPA-HF and DELIVER criteria [102][103][104][105][106][107][108]. In addition, the full implementation of dapagliflozin in real-life populations would prevent/postpone new worsening HF events or even death [102,[106][107][108]. For example, a Spanish registry of 5644 patients ≥50 years old consecutively hospitalized for HF in internal medicine departments in Spain showed that full implementation of dapagliflozin would lead to robust absolute risk reductions of mortality and HF readmission, with low NNT in patients with HF, regardless ejection fraction (Figure 7) [106][107][108].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation